2010
DOI: 10.1007/s00253-010-2932-5
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate/laccase-mediated oxidative polymerization of catechol for textile dyeing

Abstract: The synergistic effect between polyoxometalates (POMs), namely K(5)[SiW(11)V(V)O(40)]·11H(2)O and H(5)[PMo(10)V(V) (2)O(40)]·13H(2)O and laccase from ascomycete Myceliophthora thermophila has been employed for the first time in oxidative polymerization of catechol. Such a laccase-mediator system allowed the formation of a relatively high molecular weight polycatechol as confirmed by size exclusion chromatography and electrospray ionization mass spectrometry (ESI-MS) (3990 Da when using K(5)[SiW(11)V(V)O(40)]·1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
0
30
0
3
Order By: Relevance
“…Phenothiazenes, for example, have been used to initiate the polymerization of sterically demanding phenols, [32,33] or ABTS to facilitate pyrrole polymerization [34,35]. Also transition metals (e.g., Mn 2+/3+ ) [36] or polyoxometallates [37] have been reported. Second, the mediator radical itself can initiate chain growth thereby being incorporated into the polymer (see Section 2.4).…”
Section: Laccase-/peroxidase-mediator-systems (Lms/pms)mentioning
confidence: 99%
“…Phenothiazenes, for example, have been used to initiate the polymerization of sterically demanding phenols, [32,33] or ABTS to facilitate pyrrole polymerization [34,35]. Also transition metals (e.g., Mn 2+/3+ ) [36] or polyoxometallates [37] have been reported. Second, the mediator radical itself can initiate chain growth thereby being incorporated into the polymer (see Section 2.4).…”
Section: Laccase-/peroxidase-mediator-systems (Lms/pms)mentioning
confidence: 99%
“…Research in the polymerization of phenol derivatives has also used HRP [231][232][233][234][235] and lacasse [236][237][238] as catalytic enzymes. Of interest for this review is the polymerization of caffeic acid, which is found in the phenolic compounds of potato waste.…”
Section: Enzymatic Oxidativementioning
confidence: 99%
“…Laccases are the multicopper oxidases capable of catalyzing the oxidation of various organic and inorganic substrates at the presence of molecular oxygen as oxidant [16][17][18][19][20]. Recently, laccases were widely used as a biocatalyst to assist the polymerization of such monomer as aniline [21][22][23].…”
Section: Introductionmentioning
confidence: 99%